The Effectiveness of Gratitude Letter Writing Intervention on Increasing Subjective Well-Being in High School Students - Bakar, Resekiani Mas; Angreni, Afrilla Fitri; Kakiet, Ildiniah Faranita; R, M. Akbar; Muhsin, Miftahul Jannah (Polteknik Ilmu Pemasyarakatan, 2025)
Adolescence is a critical developmental stage characterized by significant physical and psychological changes that impact subjective well-being (SWB). This study explores the effectiveness of five days of gratitude letter writing intervention aimed at improving SWB among high school students. A quasi-experimental design with a pretest-posttest control group was employed involving twenty participants, divided equally into an experimental group that engaged in daily gratitude letter writing for five consecutive days, and a control group without intervention. Subjective well-being was assessed using the Satisfaction with Life Scale (SWLS) and the Positive Affect and Negative Affect Schedule (PANAS). The findings revealed no statistically significant differences between the experimental and control groups following the intervention. Despite the lack of significant improvement, the experimental group showed a positive trend in affect balance, suggesting potential benefits of the intervention. These results imply that short-term interventions may not be sufficient to produce immediate measurable changes in SWB, highlighting the importance of longer intervention periods and the inclusion of social support mechanisms. Future studies should aim to extend intervention duration and integrate social context factors to better facilitate emotional and psychological growth in adolescents. This study contributes to understanding the limitations and possibilities of gratitude-based interventions in enhancing adolescent well-being, suggesting that sustained practice and supportive environments are crucial for meaningful improvements.